First Record of Hippa adactyla (Fabricius, 1787; Crustacea, Anomura, Hippidae) from Indonesian Waters - Puji Utari Ardika; Achmad Farajallah; Yusli Wardiatno (Tropical Life Sciences Research, 2015)
Specimens of Hippa adactyla (Crustacea, Anomura, Hippidae) were collected from several coasts of Indonesia (Sumatera, Java, Bali-Lombok and Sulawesi). This finding represents the first record of this species in Indonesia and confirms its presence in the Indian Ocean and in the Wallacea region. Its systematic and morphological characteristics are described, and its distribution in Indonesia is presented. One of the main characteristics of this species is a median lobe in the anterior part of the carapace, which has 3–4 lobes. Likewise, the left antenna has 2–6 articles. Spesimen Hippa adactyla (Crustacea, Anomura, Hippidae) telah dikutip daripada beberapa pinggir laut Indonesia (Sumatera, Java, Bali-Lombok dan Sulawesi). Penemuan ini menunjukkan rekod pertama spesies ini di Indonesia dan mengesahkan kewujudannya di Lautan Hindi dan di kawasan Wallacea. Sifat-sifat sistematik dan morfologi spesies ini telah dihuraikan, dan taburannya di Indonesia telah dipersembahkan. Salah satu sifat utama spesies ini ialah lobus median pada bahagian anterior karapas yang mempunyai 3–4 lobus. Begitu juga, antena kiri mempunyai 2–6 artikel.